AB0951 MULTICENTRIC CARPOTARSAL OSTEOLYSIS SYNDROME – A RARE BUT IMPORTANT DIFFERENTIAL OF JUVENILE IDIOPATHIC ARTHRITIS. CASE REPORT OF TWO BROTHERS WITH AN IDENTICAL MAFB MUTATION. (June 2019) - Close, Rosie; Armon, Kate
Abstract : Background: Carpotarsal osteolysis is observed in a rare group of 'vanishing bone' skeletal dysplasias. Diagnosis requires a high index of suspicion combined with clinical and radiological signs. Inheritance varies amongst subtypes. Multicentric carpotarsal osteolysis syndrome (MCTO) is characterised by aggressive osteolysis in early childhood predominantly in the carpal and tarsal bones. It is associated with kidney disease in >50% which can progress rapidly to end stage renal failure. Prediction of renal impairment is not currently possible. MCTO shows an autosomal dominant inheritance pattern with heterozygous mutations in the MAFB gene. Objectives: Describe two brothers affected by MCTO highlighting the importance of a genetic diagnosis. Methods: B1 (20 years) presented age 3 years with swollen painful feet and restricted movement in his fingers and wrists and was diagnosed with polyarticular juvenile idiopathic arthritis (JIA). After no response to steroid treatment he developed rapid onset fixed flexion deformity of both elbows. He had mild learning difficulties. Based on clinical and radiological findings he was diagnosed with carpotarsal osteolyisis age 4 years. Bisphosphonates and vitamin D replacement did not halt progressive bony destruction. Consistent with the literature osteolysis stabilised in the teenage years. Renal function remains normal. B2 (5 years) is a dizygotic twin and younger sibling of B1. All other family members: parents (non-consanguineous), twin sister, sister, brother and half-brother are healthy. B2 presented aged 21 months with bilateral painful swollen wrists and reduced range of movement. His development was normal and comparable to his twin. Clinical presentation was similar to B1 who was yet to receive a genetic diagnosis. Plain films were not diagnostic as carpi unossified. Regular monitoring of renal function was advised although it was noted the nephropathy associated with MCTO does not normally manifest until the second decade. At genetic review an autosomal recessive form of carpotarsal osteolysis was considered most likely. The elbow contractures in B1 were consistent with this phenotype although subcutaneous nodules were absent. Genetic testing for MAFB gene alterations identified an identical mutation in B1 and B2 ( MFAB – c176c>Tp(Pro59leu) confirming the autosomal dominant MCTO. B2 developed hypertension, heavy proteinuria and hypoalbuminemia at 3 years, responding to tacrolimus. Results: Two brothers with clinical features of MCTO and identical mutations in MAFB gene are described. The phenotype varied significantly with early renal disease in one and mild learning difficulties in the other. Inheritance of this autosomal dominant condition in these two brothers with unaffected parents could result from either gonadal mosaicism or incomplete penetrance. There is a case of incomplete penetrance in MCTO described in the literature. [2] Conclusion: Individually skeletal dysplasias are rare yet as a group they represent an important differential to JIA requiring different management. Pursuing a genetic diagnosis in carpotarsal osteolysis is important not only for prediction of recurrence risk. It allows a definitive diagnosis to be made earlier than is possible clinically/radiologically. Significantly different phenotypes yet the same genetic mutation lends weight to the possibility of modifier genes or other epigenetic mechanisms/environmental factors affecting disease penetrance as proposed by Dworschak et al [2]. A greater understanding of these may enable prediction of renal involvement and aid development and stratification of new therapies. References: [1] Zankl, et al. Multicentric Carpotarsal Osteolysis Is Caused by Mutations Clustering in the Amino-Terminal Transcriptional Activation Domain of MAFB Am J Hum Genet 2012 9;90(3)494-501 [2] Dworschak, et al. An incompletely penetrant novel MAFB (p.Ser56Phe) variant in autosomal dominant multicentric carpotarsal osteolysis syndrome International Journal Molecular Medicine 2013 174-178 Disclosure of Interests: Rosie Close: None declared, Kate Armon Speakers bureau: Abbvie, but the fee was paid into Addenbrookes charitable account